2018
DOI: 10.3892/or.2018.6481
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of FoxP3 in a human T�cell line possessing regulatory T cell‑like function and exposed continuously to asbestos fibers

Abstract: Prompted by the known carcinogenic activity of asbestos, our investigations revealed that asbestos causes a reduction in antitumor immunity. One mechanism involves the enhancement of regulatory T (Treg) cell function and volume assayed using MT‑2 original cells (Org), an HTLV‑1 immortalized human T cell line which possesses Treg‑like function. Continuous and relatively low‑dose exposure of MT‑2 to asbestos fibers yielded sublines resistant to asbestos‑induced apoptosis and enhanced Treg function via cell‑cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This allows them to negatively select a group of potentially very damaging self reactive T cells that cannot be removed from the cortex. Mature thymocytes express only CD4 or CD8 and are known as single positive (SP) cells that leave the thymus through blood vessels at the cortical medullary junction when they enter (Maeda et al 2018). Mature at the periphery, these new T cells explore antigens present in secondary lymphoid tissues, including the spleen and lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…This allows them to negatively select a group of potentially very damaging self reactive T cells that cannot be removed from the cortex. Mature thymocytes express only CD4 or CD8 and are known as single positive (SP) cells that leave the thymus through blood vessels at the cortical medullary junction when they enter (Maeda et al 2018). Mature at the periphery, these new T cells explore antigens present in secondary lymphoid tissues, including the spleen and lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…9 Thus, we suggest that FOXP3 methylation has the potential to be a biomarker for assessment of arsenic poisoning. Additionally, the literature revealed that the aberrant DNA methylation of FOXP3 was a sensitive marker of environmental pollutants such as black carbon, 26 PM 2.5 27 , tobacco smoke, 28 and asbestos fibers, 29 and was involved in lung dysfunction or asthma caused by these pollutants through the disruption of immunosuppressive function and homeostasis of pro/anti-inflammatory. These findings added to the evidences that aberrant FOXP3 methylation may be a universal marker for the risk assessment of environmental exposure-induced inflammation-based health threats.…”
Section: Discussionmentioning
confidence: 99%
“…The Foxp3 protein plays an important role in the regulation of cytokine production through interaction with numerous proteins and transcription factors such as NFAT, nuclear factor kappa B (NF-κB, kappa-light-chain-enhancer of activated B cells) [82], and Runx1/AML1 (Runt-related transcription factor 1/acute myeloid leukemia 1 protein), also known as acute myeloid leukemia 1 protein (AML1) [83] or alpha-core binding factor 2 (CBFA2) subunit [84]. Transcription factors NFAT and Runx1/AML1 are necessary for the production of IL-2 following TCR receptor stimulation.…”
Section: Interactions Of Foxp3 Protein With Proteins and Transcriptio...mentioning
confidence: 99%